A COVER-BASED PRODUCT LINE SELECTION TO MANAGE PRODUCT LINE SIZE AND PRODUCT SIMILARITY - Park, Jungju; Lim, Ji Hyoun; Mo, Jeonghoon (International Journal of Industrial Engineering: Theory, Applications and Practice, 2018)
Product line selection is an important problem for firms who need to balance consumers’ satisfaction and costs of manufacturing and maintenance. In this paper, we revisit the problem using the concept of covering. We first identify a potential issue of product bias when product line optimization is combined with linear utility models: Many similar products could be chosen if there is no careful consideration. We propose a cover-based formulation and show that our approach can be a solution to the issue using dataset of the Korean mobile phone industry. The sensitivity results confirm the robustness of our results.